2012
DOI: 10.1007/s00381-012-1917-3
|View full text |Cite
|
Sign up to set email alerts
|

Early neurologic complications and long-term sequelae of childhood bacterial meningitis in a limited-resource country (Kosovo)

Abstract: In both study periods, the most frequent early neurologic complications of childhood bacterial meningitis were subdural effusions. Long-term sequelae were observed in 10% of children, with late seizures, neuropsychological impairment, and deafness being the most common one. Age prior to 12 months was risk factor for both early neurologic complications and long-term sequelae of bacterial meningitis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
1
9
1
1
Order By: Relevance
“…18,19 The younger age of patients have higher incidence of bacterial meningitis with neurologic complication, especially the newborn. 20 However, our study found that younger age and preterm delivery (birth history) may not be the risk factor for hydrocephalus. This is different from a study in Kosovo, 21 which found that age <12 months was a risk factor for both early neurologic complications and long-term sequelae of bacterial meningitis in children.…”
Section: Discussioncontrasting
confidence: 59%
“…18,19 The younger age of patients have higher incidence of bacterial meningitis with neurologic complication, especially the newborn. 20 However, our study found that younger age and preterm delivery (birth history) may not be the risk factor for hydrocephalus. This is different from a study in Kosovo, 21 which found that age <12 months was a risk factor for both early neurologic complications and long-term sequelae of bacterial meningitis in children.…”
Section: Discussioncontrasting
confidence: 59%
“…20 Namani S et al noted most common neurological complication of bacterial meningitis among children to be subdural effusion, recurrent seizures and hydrocephalus. 21 It was also seen that risk of neurological complications was more among infants. In the present study, we also noted that 60.2% of the children were aged less than14 months.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Kaaresen et al, Vasilopoulou et al, Namani et al, and Olson et al specified that the risk for a poor outcome was associated with early seizure that was present prior to or at the time of hospital admission. 2 , 3 , 14 , 19 For Wee et al, intensive care unit (ICU) admission or residual sequelae five years after meningitis was associated with development of seizure during the inpatient stay and required antiepileptic drugs (OR 10.6 [95% CI 1.9–60.2]). 20 Pelkonen et al associated seizures at any time point – before, during, or after hospital admission – as an independent predictor of severe neurological sequelae (OR 9.34 [95% CI 3.49–25.00]).…”
Section: Discussionmentioning
confidence: 99%